2018
DOI: 10.3892/br.2018.1083
|View full text |Cite
|
Sign up to set email alerts
|

Adenosine decreases oxidative stress and protects H2O2‑treated neural stem cells against apoptosis through decreasing Mst1 expression

Abstract: Abstract. Overproduction of free radicals during oxidative stress induces damage to key biomolecules and activates programed cell death pathways. Neuronal cell death in the nervous system leads to a number of neurodegenerative diseases. The aim of the present study was to evaluate the neuroprotective effect of adenosine on inhibition of apoptosis induced by hydrogen peroxide (H 2 O 2 ) in bone marrow-derived neural stem cells (B-dNSCs), with focus on its regulatory effect on the expression of mammalian sterile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…Various pharmacological agents and natural products targeting oxidative stress [ 45 , 46 , 47 , 48 , 49 , 50 , 51 ] have been considered in the management of neuromuscular disorders, including FRDA [ 38 , 52 , 53 ]. Adenosine and its derivatives have been reported to exhibit free radical scavenging activities [ 54 ] and protect bone marrow-derived neural stem cells against hydrogen peroxide (H 2 O 2 )-induced oxidative stress and apoptosis [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…Various pharmacological agents and natural products targeting oxidative stress [ 45 , 46 , 47 , 48 , 49 , 50 , 51 ] have been considered in the management of neuromuscular disorders, including FRDA [ 38 , 52 , 53 ]. Adenosine and its derivatives have been reported to exhibit free radical scavenging activities [ 54 ] and protect bone marrow-derived neural stem cells against hydrogen peroxide (H 2 O 2 )-induced oxidative stress and apoptosis [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that endogenous adenosine concentration increased significantly, which was positively correlated with local blood-oxygen supply [ 21 ]. In addition, Gholinejad et al found that adenosine could reduce oxidative stress by inhibiting Mst1 expression and protect neural stem cells treated with H 2 O 2 from apoptosis [ 22 ]. Inosine is a natural nucleoside derived from the degradation of adenosine, which is initially thought to have no biological effect.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, increased orexin A/hypocretin 1 peptide causes mitochondrial impairment and dysfunction, contributing to increased cellular ROS (Li et al 2020 ). Lastly, adenosine alleviates oxidative stress by increasing expression levels of an essential antioxidant gene, nuclear factor (erythroid‑derived 2)‑like 2 (Nrf2) (Gholinejad et al 2018 ), suggesting that adenosine and oxidative burden could act together to drive sleep and bring redox balance back to homeostatic levels.…”
Section: Sleep-modulating Neuropeptides Hormones and Their Connection...mentioning
confidence: 99%